The Impact of Media Attention on the Illiquidity of Stocks: Evidence from the Global FinTech Sector - Eduard Gaar; Valentin Moritz; Dirk Schiereck (Credit and Capital Markets – Kredit und Kapital, 2021)
As a result of technological innovations in data processing, the exploitation of Internet usage data in relation to search engines or social networks is becoming increasingly intriguing for understanding and anticipating stock market movements. We analyze the impact of three alternative investor attention variables, i.?e. Google search volume, Wikipedia page views, and stock market-relevant news on the rapidly growing FinTech sector. The result of the simultaneous correlation analysis reveals a highly significant correlation between the trading activities of the FinTech sector and the three investor attention variables. The time-delayed regression analysis complements the results by identifying substantial changes of the effects within one week considering the order of magnitude and sign. Furthermore, multivariate regression analysis highlights that the explanatory power for future stock trading activities and illiquidity primarily depends on Google search volume and stock market-relevant news volume, while the simultaneous correlations are best explained by the number of visits to the corresponding Wikipedia page.
Keywords: L82; L86; D82; D83; G12; G14; 330; Capital Market Liquidity; Illiquidity; Internet Search; Media Attention; FinTech